Dynamic dictators: improving the research agenda on autocratization and authoritarian resilience. Issue 6 (18th August 2021) - Sinkkonen, Elina
ABSTRACT: We do not have a comprehensive understanding of authoritarian resilience or the quality of governance globally, because we lack research analysing deepening autocratization in already authoritarian countries. Yet, deepening autocratization is an actual phenomenon affecting hundreds of millions of people worldwide. Authoritarian regimes continue to be treated as the negative end of the democracy-authoritarianism continuum, neglecting characteristics present only in authoritarian regimes. This research develops the conceptualization of deepening autocratization, as the definition of autocratization should include deepening autocratization in already authoritarian countries, rather than focusing solely on regime change. It looks at elite-level dynamics in authoritarian regimes and discusses power concentration, including proposed measures for personalization, administrative centralization, and state control over economic assets. Understanding how deepening autocratization is linked with authoritarian resilience is also crucial, as there is no "one model fits all" solution for understanding authoritarian resilience in different types of authoritarian regimes. To improve the research agenda on authoritarian resilience, research should focus on the combination of causes and their interactions rather than effects of individual causes.